Desa Digital: Pentingnya Memperkokoh Ketangguhan Desa di Era Digital - Afriyanni; Manoby, Worry Mambusy; Fitri, Suci Emilia; Pranasari, Melati Ayuning; Setyaningsih, Eny; Rosidah; Saksono, Herie (Jurnal Bina Praja, 2021)
The village is the lowest government level located in the administrative area of districts/cities municipalities throughout Indonesia. The rapid advancement of digital technology has brought global changes that require villages to carry out transformation and adaptation. In responding to this, what should be done for the sustainability of the values of life, preserving traditions, culture, and local wisdom, and building human capital to improve the welfare of its citizens? This study aims to find an extraordinary strategy to realize rural resilience through a digital village. The study used a qualitative method with case studies in two villages: i) Cijengkol Village and ii) Sepakung Village. This study finds the importance of digitalization starting from the village. The apparatus and community of Cijengkol Village are increasingly enjoying the benefits of digitization to complete various daily affairs. Meanwhile, Sepakung Village has published its natural wealth and tourism digitally. The digital village is one of the ideal solutions for rural resilience in the digital era. Human capital is the main factor. Advances in digital technology and digitalization of villages help manage village government, including the development of social life in the community in the village. Second, the village has a global presence, where digitalization has helped change the village's image and the lives of its people. It is hoped that the government will be able to initiate a participatory digital village that is responsive to the dynamics of digitalization, inclusive development, the anticipation of disasters, and digital-based environmental sustainability.